La Psicologia come Scienza della Salute Pre-atti del XII Congresso Nazionale Associazione S.I.P.S.A. Società Italiana di Psicologia della Salute. Firenze, 3-5 Novembre 2017 - CASALE, SILVIA; NERINI, AMANDA (Proceedings e report, 2017)
This volume collects the contributions presented at the XII SIPSA National Congress organized by the SIPSA Association (Italian Society of Health Psychology) and by the Department of Health Sciences of the University of Florence. The Congress aims to offer an opportunity for dialogue and discussion between scholars, researchers and professionals engaged in the field of health psychology that can stimulate a reflection on the important role of Psychology as health science. The topics will range from bioethics to e-Health, social and political interventions to counter the disparities in access to assistance and will be discussed in symposia, thematic sessions, round tables and poster sessions.